Morphological traits mediate fish occurrences in oil palm‐impacted tropical streams. (13th March 2020) - Chua, Kenny W. J.; Lim, Felix K. S.; Ahmad, Amirrudin B.; Tan, Heok Hui; Yeo, Darren C. J.
Abstract: Land‐use change is a leading driver of biodiversity loss, especially in tropical fresh waters where the conversion of natural forest to monoculture plantations impacts freshwater fish assemblages. The environmental pathways underpinning shifts in fish assemblages, however, are poorly understood, but could potentially be inferred from trait–environment relationships. We addressed this knowledge gap using eco‐morphological traits to explain fish occurrences in oil palm‐impacted streams of the Endau drainage in Peninsular Malaysia. We also investigated how traits relate to differences in environmental conditions associated with land‐use change. We then integrate findings from the above to test how potential pathways of land‐use driven environmental changes can impact species occurrences through effects on life history, feeding habits, and mobility. Mixed‐effects models show that fishes with superior (upward‐facing) mouths and low body mass were more likely to occur in oil palm streams than forest streams, and these traits were associated with grass‐dominated riparian zones and reduced woody debris in oil palm streams, respectively. Structural equation models show that mouth positions statistically mediated the effect of riparian vegetation on fish species occurrences in oil palm streams. Specifically, fishes with superior mouths were more likely to feed on terrestrial invertebrates. Our analysis of easily measurable traits revealed pathways of land‐use impact that are potentially more widely applicable than conventional taxa‐based approaches. Fishes with superior mouths tended to occur in oil palm streams as they were able to more effectively exploit inputs of terrestrial invertebrates that are potentially associated with grass‐dominated riparian vegetation. Moreover, shifts in traits may suggest land‐use driven changes in stream ecosystem functioning (e.g. in terms of the role of terrestrial subsidies), thereby informing targeted management actions in land‐use impacted habitats (e.g. retention/restoration of riparian trees).